Creativity and Industrial Cities: A Case Study of Baltimore - Zoltán J. Ács; Monika I. Megyesi (Max Planck Institute of Economics, 2007)
Creativity is changing the way cities approach economic development and formulate policy. Creative metropolises base their economic development strategies, at least partly, on building communities attractive to the creative class worker. While there are countless examples of high-tech regions transforming into creative economies, traditionally industrial cities have received much less attention in this regard. This research draws on Baltimore to assess the potential of transforming a traditionally industrial region into a creative economy. It analyses Baltimores performance on dimensions of talent, tolerance, technology, and territory both as a stand-alone metropolitan area and in comparison to similar industrial metropolises. Using data from the US Census Bureau and research on creativity measures, this case study concludes that Baltimore has the opportunity to capitalize on the creative economy because of its openness to diversity, established technology base, and appealing territorial amenities. An important consideration in the transformation towards a creative economy is Baltimore's geographic proximity and access to the largest reservoir of creative talent in the US: Washington, DC.
Keywords: 330; creativity; creative class; creativity index; creative cities; talent; technology; tolerance territory; bohemian index; gay index; old industrial cities; Baltimore; economic development; economic growth; entrepreneurship; Kreativität; Unternehmensgründung; Industriegebiet; Stadtentwicklung; Strukturwandel; Humankapital; Social Capital; Baltimore (Md.)